Perananan Dan Penerapan Data Warehouse Sebagai Pendukung Sistem Akademik Pada UIN Sumatera Utara - Azura, Rizky; Pasaribu, Indriyani; Putri, Sella Permana; Nurbaiti, Nurbaiti (Jurnal Sains dan Teknologi (JSIT), 2023)
A data warehouse is where information can be stored for a very large scope, and in a comprehensive manner. Academic divisions can utilize the data warehouse's ability to aggregate data, which makes it easier for them to provide information to support evaluation and decision analysis procedures. The problem was that in the scientific division, the information warehouse was not accessible and could not provide important reports of the instruction and assessment process. The design of the data warehouse provides strategic information such as the number of new students in each batch and student status. The purpose of this research is to overcome the obstacles in implementing data from various different sources into the data warehouse. The method used in this research is a qualitative method that provides breadth in exploring in-depth and contextual information. The result of this research is to facilitate the academic system of UIN-SU to serve important information aimed at the academic division to process historical data and present accurate information for evaluation and decision making.